Mulher e o mundo do trabalho: histórias de vida de estudantes no Programa Nacional Mulheres Mil Instituto Federal de Educação, Ciência e Tecnologia do Tocantins IFTO - Amorim, Janaína Miranda Muradás (2015)
The present dissertation had the purpose to study the life history of women that participate in professional training courses, offered in the campuses: Palmas and Porto Nacional, in the Federal Institute of Education, Science and Technology of Tocantins, through the National Program Mulheres Mil . The analyzed aspects were based on the course of their educational and sociocultural relations, but also on the achievement process to the employment. The overall objective was to understand how these students redefined their life histories, both by living in social and educational spaces, and by personal and collective relations, by influences or not, positive or negative and if, after finishing the course, they sought employment. Thus, the reasons for entering the institution and/or the interruption of the course were investigated. These points contributed to elaborate the women s profile that participated in the classes of Camareira (campus Palmas) and informática para o espaço doméstico e trabalho (campus Porto Nacional) in the period from 2012 to 2013. The methodological procedures used were the Oral History (MEIHY, 2002), with Life History techniques (PINEAU, 2011) and the biography reaserch (SCHÜTZE, 2010), following: narrative interviews and reports from the women s speech. In this way, with the evidenced results by the reports from the local women, it was allowed to meet them, comprehend their life histories and the future expectations. Furthermore, it can be concluded that living in the school space can redefine life.